Proof-of-principle of a new geometry for sampling calorimetry using inorganic scintillator plates. (13th February 2015) - Becker, R; Dissertori, G; Gendotti, A; Huang, Q; Luckey, D; Lustermann, W; Lutterer, S; Nessi-Tedaldi, F; Pandolfi, F; Pauss, F; Peruzzi, M; Quittnat, M; et al.
Abstract: A novel geometry for a sampling calorimeter employing inorganic scintillators as an active medium is presented. To overcome the mechanical challenges of construction, an innovative light collection geometry has been pioneered, that minimises the complexity of construction. First test results are presented, demonstrating a successful signal extraction. The geometry consists of a sampling calorimeter with passive absorber layers interleaved with layers of an active medium made of inorganic scintillating crystals. Wavelength-shifting (WLS) fibres run along the four long, chamfered edges of the stack, transporting the light to photodetectors at the rear. To maximise the amount of scintillation light reaching the WLS fibres, the scintillator chamfers are depolished. It is shown herein that this concept is working for cerium fluoride (CeF3 ) as a scintillator. Coupled to it, several different types of materials have been tested as WLS medium. In particular, materials that might be sufficiently resistant to the High- Luminosity Large Hadron Collider radiation environment, such as cerium-doped Lutetium- Yttrium Orthosilicate (LYSO) and cerium-doped quartz, are compared to conventional plastic WLS fibres. Finally, an outlook is presented on the possible optimisation of the different components, and the construction and commissioning of a full calorimeter cell prototype is presented.